Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Kelas VIII di SMP Nahdhotul Ulama’ Sunan Giri Kepanjen Malang - Alif Achadah (IAI Darussalam, 2019)
Motivation strategy in learning is a planning towards motivation which contains a series of activities that are specifically designed and designed, to achieve various specific educational goals. Therefore, to achieve the desired educational program objectives in accordance with educational values. So that the teacher is expected to have several motivational learning strategies that can inspire students to learn comfortably, pleasantly and not monotonously. To achieve the goal of increasing student motivation, a better effort is needed from the teacher in choosing and applying motivational strategies, methods and learning media that are in accordance with these competencies. The purpose of this study is: a). Describing the teacher's strategies applied in increasing student learning motivation in class VIII Islamic Education subjects at NU Sunan Giri Kepanjen Middle School. b). Describe changes in the increase in learning motivation of VIII graders in NU Middle School Sunan Giri Kepanjen